2013
DOI: 10.1002/pds.3468
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adverse drug reactions using hospital databases—a nationwide study in Portugal

Abstract: Several methods have been used for the detection of ADRs, but they are difficult to apply at a national level. Spontaneous reporting is widely used but grossly underestimates the frequency of ADRs. The database methodology can be very useful to estimate ADRs frequency and to perform a simple characterization of ADRs nationwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
(40 reference statements)
5
24
2
3
Order By: Relevance
“…This is consistent with the major drugs groups most frequently associated with ADRs identified from external code as neutropenia was common side effect of antineoplastic drugs and systematic antibiotic while hypoglycemia was common side effect of insulin. In addition, our findings were similar to those of the previous study 14 , which found that neutropenia, hypoglycemia were the common ADRs found from hospital database. According to our results, caution should be made to monitor safety among patients who were prescribed with those drugs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with the major drugs groups most frequently associated with ADRs identified from external code as neutropenia was common side effect of antineoplastic drugs and systematic antibiotic while hypoglycemia was common side effect of insulin. In addition, our findings were similar to those of the previous study 14 , which found that neutropenia, hypoglycemia were the common ADRs found from hospital database. According to our results, caution should be made to monitor safety among patients who were prescribed with those drugs.…”
Section: Discussionsupporting
confidence: 82%
“…When looking at trend of ADRs, similar to the previous studies [14][15][16]19 , we found that incidence of ADR-related hospital admission was increasing, which might be due to the introduction of new drugs, poly-pharmacotherapy, increasing aging population, and improvement of diagnostic and coding practice.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This corresponds to less than 1% of all hospitalizations of children during this period. Although this rate is consistent with previous reports based on administrative databases [20], it is considerably lower than rates found by studies that have used other methodological approaches. In one chart review study, for example, approximately 16% of inpatients had a penicillin allergy label in their medical records [21].…”
Section: Discussionsupporting
confidence: 62%
“…A recent meta-analysis [5] has indicated that ADRs may occur in 16.88% of hospitalized patients. In Portugal, 16,720 ADRs were identified among 9,271,122 hospitalizations between 2000 and 2009, representing 1.26% of the total hospitalized patients [6]. By improving the predictability of drug response in individual patients through the application of genetic information in guiding drug therapy decisions, it will be possible to avoid ADRs and to improve drug efficacy and safety [7].…”
Section: Introductionmentioning
confidence: 99%